The selection of appropriate cultural conditions for growth of recombinant green microalga Chlamydomonas reinhardtii in laboratory condition - Hong, Dang Diem; Tam, Luu Thi; Thom, Le Thi; Lan Anh, Hoang Thi; Thu, Ngo Thi Hoai; Thu, Ha Thi; Huong, Nguyen Minh; Quyen, Dong Van (Academia Journal of Biology, 2018)
The green alga Chlamydomonas reinhardtii is a model organism for studying mechanism of the body in response to changes in environmental conditions, photosynthesis as well as chloroplast biogenesis and can be modified to produce high value proteins. In this study, we present results on the selection of cultural conditions for the growth of cell wall - deficient mutant C. reinhardtii (503 strain- control) and recombinant 503-2 strain expressing VP28 protein of White Spot Syndrome Virus (WSSV) in 250 ml flasks. Suitable conditions for the growth of both control and recombinant strains were TAP medium, temperature of 25 C, pH = 7, light intensity of 2 klux, C source - Trisbase, N source - nitrate and salinity of 50 - 100 mM. In these conditions, maximum cell density of the control and recombinant strains was 3.20 ± 0.08 x 106 and 2.96 ± 0.17 x 106 cells/ mL after 3 and 7 days of cultivation, respectively. The presence of vp28 gene in the recombinant microalgal strain was stably maintained at all levels of culture. The results of this paper will be a scientific basis for culturing the recombinant C. reinhardtii to obtain algal biomass which had high expression of surface VP28 protein of WSSV’s envelope for edible vaccine production vaccine by feeding in order to prevent white spot disease of shrimp.